FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA ROOMBOY DI TURI BEACH RESORT BATAM - Simanjuntak, Juli Yanto Wibowo; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to determine the factors that influence the performance of roomboys at Turi Beach Resort Batam. This research uses a qualitative method with a qualitative descriptive approach to describe and explain the situation that occurred by collecting data and information in the field. The key informants in this research are SPV Room and Roomboy employees. In this research, the data collection techniques used were interviews, observation and documentation. Based on the research results, it can be concluded. Romboy Turi Beach Resort Batam has six factors that influence Roomboy performance, namely work equipment, skills and experience, building shape, room facilities, room cleaning techniques and supervision. Of these six factors, the average respondent strongly agrees that these factors influence the performance of Roomboy at Turi Beach Resort Batam. However, there was one factor where the informants did not agree, namely the room facilities factor, but only one informant disagreed out of the four informants. The building shape factor really influences the performance of Roomboy at Turi Beach Resort Batam because Turi Beach Resort Batam is famous for its building shape and the distance between rooms is quite far. This makes Roomboys have a bit of a problem, especially Roomboys who are quite old because they get tired easily when cleaning from one room to another. Keywords: Factors, Performance, Turi Beach